The influence of employee empowerment on employee performance in public higher education institution / Nur Syuhada Anuar - Anuar, Nur Syuhada (Faculty of Business and Management, 2018)
Employee performance is an indicator of organization’s performance which means that if employee performance is poor, it also leads to decrease in the performance of the organization, and otherwise. Based on study on employee performance in administrative and support services by Department of Statistics Malaysia in 2017, it shows that an increment of 13.8 per cent per annum with a value of RM 10.5 billion of value added in a row with the value of gross output. It connotes that an improvement in employee performance from period of 2010 to 2015. In contrast, Nicholas Cheng (2013) said expert reported that Malaysian workers short of performance culture that caused low productivity as compared to other countries in the world. Therefore, the aim of this study is to foresee the influence of employee empowerment on employee performance. The objectives of the study are to determine whether employee participation influence employee performance, to investigate the impacts of training and development toward employee performance, to examine the influence of reward system on employee performance and to identify the effects of communication system toward employee performance. A descriptive study was adopted with a focus on qualitative characteristics of employee empowerment includes employee participation, training and development, reward system and communication system on employee performance. The population of interest is 160 employees in a public higher education institution. A sample size of 113 employees was sampled based on Krejcie and Morgan (1970). For the analysis, primary data collected using questionnaire. The result revealed that there is no significant relationship between all dimension of employee empowerment with employee performance.